The Effect of Support Group Method on Quality of Life in Post-menopausal Women - S ESmaeilzadeh; AF Hosseini; ES Merghaati Khoei; M Keshavarz; M Yazdkhasti; M Amiri Pebdani; H Jafarzadeh (Tehran University of Medical Sciences, 2012)
Background: Quality of life in post-menopausal women and menopausal symptoms are closely related concepts. Influence health education policy in order to promote health and adopt a menopause lifestyle requires alternative strategies, including health training programs with community - based interventions. The current study aims to survey the effects of support groups on quality of life of post-menopausal women.Methods: A blind field trial (2010) was conducted at Saadatmandii Clinical Center (Robat Karim, Iran). 110 women were selected randomly divided into test and control groups (consisting of 55 ones). Menopause specific quality of life questionnaire (MENQOL) was used for evaluation of life quality before and three months after intervention; there was no intervention in the control group. Data were analyzed by using SPSS/16. Qualitative variables were analyzed using chi-square tests and quantitative variables were analyzed using Mann-Whitney and Wilcoxon test, paired T-test and independent t-test.Results: There was significant difference between vasomotor, psychosocial, physical, sexual aspects and life quality of this group pf women (P<0.001). There was no statistically significant difference in the quality of life of women in control group.Conclusion: According to the results method of support group can lead to improved quality of life for post-menopausal ones and it can be appropriate healthcare policy to promote health and improve life quality of this group of women.